2016
DOI: 10.1016/j.tine.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Idea units in notes and summaries for read texts by keyboard and pencil in middle childhood students with specific learning disabilities: Cognitive and brain findings

Abstract: Seven children with dyslexia and/or dysgraphia (2 girls, 5 boys, M=11 years) completed fMRI connectivity scans before and after twelve weekly computerized lessons in strategies for reading source material, taking notes, and writing summaries by touch typing or groovy pencils. During brain scanning they completed two reading comprehension tasks—one involving single sentences and one involving multiple sentences. From before to after intervention, fMRI connectivity magnitude changed significantly during sentence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…A recent study showed that for students with dyslexia of comparable age as in the current study, computer-presentation of text to be read so that each sentence is presented one word at a time (eliminating the distractibility from other words in a sentence) resulted in better reading comprehension than presenting each sentence one added word at a time (allowing for the possibility of regressions out due to distractibility from other visually displayed words (authors, manuscript in preparation). Also the DTI results of the current study show the relationship of language by hand (writing) and language by eye (reading) for the dysgraphia group, consistent with much cognitive research showing a writing-reading relationship, including the benefits of note taking in handwriting for reading comprehension [ 47 ].…”
Section: Discussionsupporting
confidence: 87%
“…A recent study showed that for students with dyslexia of comparable age as in the current study, computer-presentation of text to be read so that each sentence is presented one word at a time (eliminating the distractibility from other words in a sentence) resulted in better reading comprehension than presenting each sentence one added word at a time (allowing for the possibility of regressions out due to distractibility from other visually displayed words (authors, manuscript in preparation). Also the DTI results of the current study show the relationship of language by hand (writing) and language by eye (reading) for the dysgraphia group, consistent with much cognitive research showing a writing-reading relationship, including the benefits of note taking in handwriting for reading comprehension [ 47 ].…”
Section: Discussionsupporting
confidence: 87%
“…On the one hand, this finding may be due to reading problems of some but not all of the students with diagnosed specific learning disabilites in transcription by the research team. On the other hand, this finding may be due to lack of prior explicit instruction in strategies of taking notes and writing summaries, which has been shown to be effective for students with specific learning disabilites in written language, including, but not restricted to, transcription disabilities (Richards et al, 2016). That is, explicit strategies in translation at different levels of language may need to be supplemented with explicit strategies with note taking and summary writing to facilitate written summaries in students with specific learning disabilites in transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence regarding altered functional connectivity following reading intervention suggests that integrating dispersed functional networks facilitates reading improvements in RD ( Perdue et al, 2022 ). Intervention-related neuroplasticity effects were found both during task-based and resting-state fMRI in diverse brain systems including fronto-parietal and cingulo-opercular networks ( Horowitz-Kraus et al, 2015 ; Richards et al, 2016 , 2017 ), and among low-level visual, dorsal attentional, and executive function networks distributed in various brain regions ( Horowitz-Kraus et al, 2019 ).…”
Section: Reading Intervention and Neuroplasticitymentioning
confidence: 99%